Preconditions for Construction of Observatory in the Kiev University Named After St. Vladimir (to the 170th anniversary of foundation) - Salata, S.A. (Питання історії науки і техніки, 2014)
In 2015 the scientific community of our country will celebrate the 170th anniversary of
foundation of the Astronomic Observatory in the Kiev University of St. Vladimir.
The article gives a short overview of preconditions of the Kiev University founding (the
sixth on the territory of the Russian Empire). The role of the famous astronomer-scientist V.F.
Fedorov (the first director) is exposed in decision making on the necessity of organization of
observatory. His activity in cooperation with the civil architect V.I. Beretti in the choice of the
territory and construction of the observatory as well is also shown. В 2015 году научная общественность нашей страны будет отмечать 170-летие
основания при Киевском университете Св. Владимира Астрономической обсерватории.
В данной статье кратко изложены предпосылки открытия университета в
Киеве (шестого на территории царской России). Показана роль известного ученого-астронома В.Ф. Федорова (первого директора) в решении вопроса о необходимости организации обсерватории. Освещена его деятельность в содружестве со знаменитым архитектором В.И. Беретти в выборе территории и строительстве самой обсерватории.